Relationship between sports participation and the level of motor coordination in childhood: A longitudinal approach - Vandorpe, B.; Vandendriessche, J.; Vaeyens, R.; Pion, J.; Matthys, S.; Lefevre, J.; Philippaerts, R.; Lenoir, M. (Journal of Science and Medicine in Sport, 2012)
Objectives: This study examined the stability of motor coordination and the relationship between motor coordination and organized sports participation over time. Design: Longitudinal design. Methods: A total of 371 children between six and nine years of age at initial testing completed a test battery measuring motor coordination in three consecutive years and a questionnaire on their club sports participation in year 1 and year 3 of testing. Results: Correlation coefficients revealed the motor coordination of children to be a highly stable factor, ranging from 0.662 (6-8 years) to 0.873 (7-9 years). Results of the Repeated Measures ANOVA indicated that children who consistently practiced sports in a club environment over the three years of testing displayed better coordination levels than children who only partially participated or did not participate in a club environment at all. Moreover, stability was further indicated as consistent sports participation over time and changes or lack thereof did not substantially influence the development of motor coordination over time. In addition, the basic level of motor coordination and the amount of club sports participation significantly predicted sports participation two years later. Conclusion: The importance of the stability of motor coordination levels in childhood and its role in determining organized sports participation may have implications for talent identification purposes as well as potential health-related benefits in childhood and throughout the lifespan.